Structures of the human adult muscle-type nicotinic receptor in resting and desensitized states - Anna Li; Ashley C.W. Pike; Richard Webster; Susan Maxwell; Wei-Wei Liu; Gamma Chi; Jacqueline Palace; David Beeson; David B. Sauer; Yin Yao Dong (Cell Reports)
Summary: Muscle-type nicotinic acetylcholine receptor (AChR) is the key signaling molecule in neuromuscular junctions. Here, we present the structures of full-length human adult receptors in complex with Fab35 in α-bungarotoxin (αBuTx)-bound resting states and ACh-bound desensitized states. In addition to identifying the conformational changes during recovery from desensitization, we also used electrophysiology to probe the effects of eight previously unstudied AChR genetic variants found in patients with congenital myasthenic syndrome (CMS), revealing they cause either slow- or fast-channel CMS characterized by prolonged or abbreviated ion channel bursts. The combined kinetic and structural data offer a better understanding of both the AChR state transition and the pathogenic mechanisms of disease variants.